2014
DOI: 10.1002/macp.201300762
|View full text |Cite
|
Sign up to set email alerts
|

The Renaissance of Side‐Chain Ferrocene‐Containing Polymers: Scope and Limitations of Vinylferrocene and Ferrocenyl Methacrylates

Abstract: The synthesis of metal‐containing polymers and block copolymers has led to a rapidly expanding field of research interest for manifold potential applications. Within this contribution, some recent advances in the field of side‐chain ferrocene‐containing polymers focusing on poly(vinylferrocene) and poly(ferrocenyl methacrylates) are presented. The synthetic developments shown focus on living and controlled polymerizations, as well as surface‐initiated polymerization strategies. First attempts and recent develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…The development of PFS materials has also helped stimulate further development of other polymer systems with metallocene side groups, such as poly(vinylferrocene), poly(ferrocenylmethacrylates), and related materials, 406,407 and also side chain polycobaltocenes. 408 Importance advances in these areas with respect to living polymerisation, self-assembly, and applications have been recently reported.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…The development of PFS materials has also helped stimulate further development of other polymer systems with metallocene side groups, such as poly(vinylferrocene), poly(ferrocenylmethacrylates), and related materials, 406,407 and also side chain polycobaltocenes. 408 Importance advances in these areas with respect to living polymerisation, self-assembly, and applications have been recently reported.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…The authors found that the introduction of -CF 3 groups at the end of hb polyimide increased oxygen and nitrogen permeability, whereas the selectivity decreased in the presence of the terminal groups. The B 3 monomer TFAPOB (1-17, Scheme 9a) was further utilized by Zhang and colleagues [142] together with 4,4 0 -oxydiphthalic anhydride (ODPA) as A 2 monomer to form fluorinated hb-PIs by the A 2 + B 3 approach. Fluorinated hb-PIs end-capped with metallophthalocyanines were prepared by the reaction of dicyanophenyl end-capped fluorinated hb-PI with excessive amounts of 1,2-dicyanobenzene and the corresponding metal (Cu, Zn, Ni) salt in quinoline.…”
Section: Hyperbranched Polyimidesmentioning
confidence: 99%
“…A variety of polymerization methods have been used since the first ferrocene-containing polymers were obtained by free radical polymerization of vinyl ferrocene in 1967. 3 In comparison, due to the inherent stability of 18-electron species, 19-e cobaltocene can lose one electron easily to form the much more stable 18-e cobaltocenium cation. Besides some advantageous properties such as high chemical stability, the isoelectronic cobaltocenium monomers and polymers show high solubility in water with the use of hydrophilic counterion, which could be more beneficial for applications in green chemistry and biomedical areas.…”
mentioning
confidence: 99%
“…It might be possible that the methylene group in α -position to the ferrocene unit in FeMMA was activated toward H-abstraction by a radical and gave rise to side reactions of chain transfer. 3d We then synthesized another ferrocene monomer without α -hydrogen: 2-(methacrylolyoxy)ethyl ferrocenecarboxylate (MAEFe). As shown in the 1 H NMR spectrum of MAEFe, protons of Cp rings can be found at ∼4.7, ∼4.4, and ∼4.2 ppm, and the peaks at ∼6.0 and ∼5.5 ppm were assigned to two vinyl protons from the methacrylate double bond (Figure 2a).…”
mentioning
confidence: 99%